2013
DOI: 10.1175/jpo-d-12-081.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remote Generation Sites on Model Estimates of M2 Internal Tides in the Philippine Sea*

Abstract: This study investigates the impact of remotely generated internal tides on model estimates of barotropic to baroclinic tidal conversion for two generation sites bounding the Philippine Sea: the Luzon Strait and the Mariana Island Arc. A primitive equation model is used to characterize the internal tides generated by the principal semidiurnal tide (M 2 ) over a domain encompassing the two generation sites. Energetic internal tides are generated at the Luzon Strait where nearly 17 GW of barotropic tide energy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
93
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 54 publications
18
93
1
Order By: Relevance
“…There is a rich modal structure to the internal tide fluctuations at both diurnal and semidiurnal frequencies, but unlike the random diffuse internal waves, the internal tide modes have strong correlations. The observation of an internal tide field not dominated by mode 1 is consistent with the recent numerical modeling by Kerry et al (2012) who quantified significant energy in modes 1 through 3 for Philippine Sea M2 internal tides. Note that aside from an energy level shift, in which diurnal dominates at the DVLA and vice versa for T1, the energy distributions for DVLA and T1 have very similar shapes.…”
Section: B Internal Tidessupporting
confidence: 90%
See 1 more Smart Citation
“…There is a rich modal structure to the internal tide fluctuations at both diurnal and semidiurnal frequencies, but unlike the random diffuse internal waves, the internal tide modes have strong correlations. The observation of an internal tide field not dominated by mode 1 is consistent with the recent numerical modeling by Kerry et al (2012) who quantified significant energy in modes 1 through 3 for Philippine Sea M2 internal tides. Note that aside from an energy level shift, in which diurnal dominates at the DVLA and vice versa for T1, the energy distributions for DVLA and T1 have very similar shapes.…”
Section: B Internal Tidessupporting
confidence: 90%
“…Internal tides are also known to fill the world ocean and they are particularly energetic where barotropic tidal currents cross abrupt topography (M€ uller and Liu, 2000). In the Philippine Sea, the Luzon Strait and Mariana Islands Arc are known to be active but variable generation sites for internal tides (Ramp et al, 2010;Zhang et al, 2011;Li and Farmer, 2011;Kerry et al, 2012). Unlike GM-like internal waves, internal tides can be modeled more or less deterministically using regional models that carefully treat the sensitive topographic generation processes and the inherent modulation from eddies and fronts (Merrifield and Holloway, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[2009] reported that the biogeochemical environment on the southern Taiwan shelf is affected by internal tides generated in the Luzon Strait. In addition, recent modeling studies revealed that internal tides coming from remote sources may cause fluctuations in local stratification, and thus affect the barotropic to baroclinic conversation [Kelly and Nash, 2010;Kerry et al, 2013Kerry et al, , 2014. Internal tides are an important energy source for the abyssal ocean mixing.…”
Section: Introductionmentioning
confidence: 99%
“…They found that barotropic to baroclinic energy conversion for the M 2 tide was 9.6 GW with 2.3 GW propagating eastward. Most recently, Kerry et al (2013) and Powell et al (2013), using the regional ocean modeling system (ROMS), found that 17 GW of M 2 barotropic tidal energy is converted into internal tides in the Luzon Strait with 4.8 GW propagating eastward into the Philippine Sea (Fig. 3).…”
Section: A Physical Oceanographymentioning
confidence: 99%
“…The westwardpropagating eddies interact with an intense western boundary current, the Kuroshio, that flows northward to the east of Taiwan. Large internal tides generated in Luzon Strait between Taiwan and the Philippines and at the Mariana Island Arc to the east propagate into the region (Niwa and Hibiya, 2004;Jan et al, 2008;Zhao and D'Asaro, 2011;Kerry et al, 2013). Typhoons regularly cross the Philippine Sea during summer and fall affecting the structure of the upper ocean.…”
Section: Introductionmentioning
confidence: 99%